Perancangan Sistem Informasi Antrian Berbasis Web Pada puskesmas Selangit - Alfero, Aldi; Sujana, Dadang; Anam, Muhammad Khoirul (Jurnal Ilmiah Fakultas Teknik, 2025)
The Selangit Health Center is a health center that stands in the Selangit District, Musirawas Regency, South Sumatra which includes 11 villages in which, From the results of observations made, every day there are approximately 70 patients queuing for the Selangit Health Center doctor’s visit. This of course makes patients who are waiting uncomfortable because they are waiting for a queue that is quite long until it arrives when the queue number is mentioned and an examination is carried out by a doctor. Conventional queues often present challenges, such as errors when calling the queue to be served. One of the health service centers at the Selangit District Health Center is developing a manual queuing system, however, the puskesmas staff still accepts patient calls. The waterfall method is used in this study. The purpose of making this system is to organize and facilitate data collection of patients who need services by managing queues more effectively. for the results in several tests on the community, the system that was made functioned properly and was easy to understand by the exorbitant community and when testing by officers on the system that was made there were several results obtained, which were very helpful in inputting data on Selangit Health Center patients who previously needed books and pens for recording patient data now don’t need that anymore because this system has been created, the time needed is less because it only takes 1 time to collect data, so there is no need for repeated data collection and it reduces queue buildup at the health center because information is easy to get the queue that is currently running at the health center by the community, and for the application itself a trial has been carried out on 10 testers selected from various circles of society and obtained valid results (can be run properly). % of tasks that were successfully carried out by the audience / testers, which means that the system created was well received